GTPase Activity Plays a Key Role in the Pathobiology of LRRK2 - Xiong, Yulan (Public Library of Science, 2010)
Mutations in the leucine-rich repeat kinase 2 (LRRK2) gene are associated with late-onset, autosomal-dominant, familial Parkinson's disease (PD) and also contribute to sporadic disease. The LRRK2 gene encodes a large protein with multiple domains, including functional Roc GTPase and protein kinase domains. Mutations in LRRK2 most likely cause disease through a toxic gain-of-function mechanism. The expression of human LRRK2 variants in cultured primary neurons induces toxicity that is dependent on intact GTP binding or kinase activities. However, the mechanism(s) underlying LRRK2-induced neuronal toxicity is poorly understood, and the contribution of GTPase and/or kinase activity to LRRK2 pathobiology is not well defined. To explore the pathobiology of LRRK2, we have developed a model of LRRK2 cytotoxicity in the baker's yeast Saccharomyces cerevisiae. Protein domain analysis in this model reveals that expression of GTPase domain-containing fragments of human LRRK2 are toxic. LRRK2 toxicity in yeast can be modulated by altering GTPase activity and is closely associated with defects in endocytic vesicular trafficking and autophagy. These truncated LRRK2 variants induce similar toxicity in both yeast and primary neuronal models and cause similar vesicular defects in yeast as full-length LRRK2 causes in primary neurons. The toxicity induced by truncated LRRK2 variants in yeast acts through a mechanism distinct from toxicity induced by human α-synuclein. A genome-wide genetic screen identified modifiers of LRRK2-induced toxicity in yeast including components of vesicular trafficking pathways, which can also modulate the trafficking defects caused by expression of truncated LRRK2 variants. Our results provide insight into the basic pathobiology of LRRK2 and suggest that the GTPase domain may contribute to the toxicity of LRRK2. These findings may guide future therapeutic strategies aimed at attenuating LRRK2-mediated neurodegeneration.